A dynamic reaction density functional theory for interfacial reaction-diffusion coupling at nanoscale. (8th June 2021) - Tang, Weiqiang; Yu, Hongping; Zhao, Teng; Qing, Leying; Xu, Xiaofei; Zhao, Shuangliang
Highlights: A dynamic reaction density functional theory for interfacial RD process is proposed. DRxDFT is developed by combining the DDFT with reaction collision theory. An irreversible model reaction on a catalytic substrate is demonstrated. Abstract: Reaction-diffusion (RD) coupling lies in the heart of chemical engineering. Due to the inherent density inhomogeneity of interfacial systems, the existing continuum approaches for quantifying the coupling between reaction and diffusion do not translate into interfacial systems, which highlights the urgent need for developing new methods to describe the RD coupling at nanoscale. In this work, a dynamic reaction density functional theory (DRxDFT) is proposed by combining the classical dynamic DFT for describing reactant/product diffusion with the reaction collision theory for addressing chemical reaction. For demonstrating its applicability to interfacial systems, the DRxDFT is hereafter applied to investigate an irreversible model reaction A + 2B → 2C on a catalytic substrate, and the effects of temperature, substrate adsorption strength, reactant concentration, diffusion coefficient, and reaction activation energy on reaction efficiency are examined. The calculated results show that the enhancement of reaction efficiency weakly depends on the unilateral increase of reaction or diffusion rate, but is strongly determined by the incensement of the coupled degree of reaction and diffusion. The proposed theory provides a promising tool for guiding the optimization and intensification of interfacial RD processes.